Bilateral dependence of sleep disorders and temporal lobe epilepsy – literature review - Magdalena Drabik; Marek Sarnacki; Barbara Miziak (Medycyna Ogólna i Nauki o Zdrowiu, 2021)
Introduction The analysis of sleep and its phases in the context of various pathophysiologies has attracted increasing attention from the scientific community; therfore, this review of the literature focuses on temporal lobe epilepsy (TLE).